Unveiling the State of Mental Health in Finland: Insights, Challenges, and Pathways to Well-Being - Lampinen Mishina; Lilja Eino (International Journal of Science and Society, 2023)
In the serene landscapes of Finland, a nation renowned for its quality of life, this journal article delves into the intricate tapestry of mental health. Titled "Unveiling the State of Mental Health in Finland: Insights, Challenges, and Pathways to Well-Being," this study offers a comprehensive exploration of Finland's mental health landscape. Through a mixed-methods approach, it examines the prevalence of mental health issues, demographic and socioeconomic factors shaping mental well-being, and the impact of cultural and regional variations. The study investigates the effectiveness of existing mental health initiatives while acknowledging the persistent gaps. It also provides a comparative analysis with international models, shedding light on valuable insights and lessons. The article underscores Finland's commitment to nurturing mental well-being, reducing stigma, and ensuring access to support. As Finland continues its journey, it offers inspiration and knowledge to nations worldwide striving to prioritize mental health as a fundamental aspect of human flourishing.